Upaya Guru Bimbingan Konseling Dalam Mengatasi Kekerasan Verbal Pada Peserta Didik Kelas VIII SMP Negeri 4 Kota Kupang - Bergita Inda Inda; Khetye R Saba; Andriyani E Lay (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2025)
Verbal violence often occurs anywhere in the family, community, and educational institutions. One of them is at SMPN 4 Kupang City. The phenomenon that researchers found in the field was that there were students who committed verbal violence and there were those who became victims of verbal violence. Verbal violence is carried out in the form of making fun of friends, cursing at friends, humiliating friends and there are students who experience verbal violence in the form of shouting and cursing. This research aims to determine the efforts of guidance and counseling teachers in dealing with verbal violence in class VIII students at SMPN 4 Kupang City. The approach and type of research used in this research is qualitative, with a case study type of research. The data collection techniques used in this research are interviews, observation and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The data validation techniques that researchers use are source triangulation and technical triangulation. The results of the research show that there are forms of violence carried out by students such as insulting friends, threatening friends, humiliating friends, insulting or making fun of friends (bullying), cursing friends. The reasons students commit violence are because they want to gain recognition, peer influence, and unstable emotional conditions. Efforts made by guidance and counseling teachers such us providing individual counseling services, using a personal approach, collaborating with school officials.